Investigation and Comparison of the Effect of Facts Devices, Capacitors and Lines Reactance Variations on Voltage Stability Improvement and Loadability Enhancement in Two Area Power System - Navid Ghaffarzadeh; Haniyeh Marefatjo; Iman Soltani (Institute of Advanced Engineering and Science, 2012)
This paper studies the important power system phenomenon and voltage stability by using continuation power flow method. Voltage collapse scenario is presented which can be a serious result of voltage instability and also the parameters that affected by voltage collapse are discussed. In analyzing power system voltage stability, continuation power flow method is utilized which consists of successive load flows. In this paper steady-state modeling of Static VAR Compensator (SVC) and Unified Power Flow Controller (UPFC) and effect of compensator and variation of line reactance on the voltage stability have been studied and Comparison between performance of UPFC and SVC and installation shunt capacitor and variation of line reactance for improve voltage stability has been done.Case studies are carried on 11 bus network in two areas. Simulation is done with PSAT in MATLAB. Continuation Power Flow was implemented using Newton Raphson method. Simulation results show the proper performance of UPFC, SVC, installation shunt capacitor and variation of line reactance to improve voltage control and significantly increase the loadability margin of power systems.